2016
DOI: 10.15243/10.15243/jdmlm.2016.034.631
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of crops residues as compost and biochar for improving soil physical properties and upland rice productivity

Abstract: Abstract:The abundance of crops waste in the agricultural field can be converted to organic fertilizer throughout the process of composting or pyrolysis to return back into the soil. The study aimed to elucidate the effect of compost and biochar application on the physical properties and productivity of upland rice at Village of Sukaraja Nuban, Batanghari Nuban Sub district, East Lampung Regency in 2015. The amendment treatments were A. control; B. 10 t rice husk biochar/ ha; C. 10 t maize cob biochar/ha; D. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 13 publications
(17 reference statements)
5
5
1
1
Order By: Relevance
“…In contrast, biochar amendment stood out from compost in the context of lowering Bb and these findings are in agreement with (Agegnehu et al, 2015), this may signify that biochar might be substantially lighter than compost. In contrast to our results, Barus (2016) observed that compost addition stood out from biochar in the context of decreasing Bd; nevertheless, trial was set for 1 month, indicating that biochar addition become more effective in the soil with time prolongation.…”
Section: Soil Bulk Densitycontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast, biochar amendment stood out from compost in the context of lowering Bb and these findings are in agreement with (Agegnehu et al, 2015), this may signify that biochar might be substantially lighter than compost. In contrast to our results, Barus (2016) observed that compost addition stood out from biochar in the context of decreasing Bd; nevertheless, trial was set for 1 month, indicating that biochar addition become more effective in the soil with time prolongation.…”
Section: Soil Bulk Densitycontrasting
confidence: 99%
“…All the amendments tested; compost and biochar additions, were able to decrease Bd and these results are consistent with (Agegnehu et al, 2015); the impact might be a result of light material additions (i.e. compost and biochar), which are commonly endowed with a lower bulk density (Ouyang et al, 2013) and an increasing of porosity (Barus, 2016) due to highly porous material additions, which might have made the experimental soil become increasingly light and herein lies the root of decreasing Bd. Additionally, increased of SOM as indicated in Fig.…”
Section: Soil Bulk Densitysupporting
confidence: 66%
See 3 more Smart Citations